(3TQM MOjK(B: (3ef YQa faSg abO YQa QHgs - (3GdUbQj, GdeWjQaj, GdGMSGFj, GdHMQGfj, YeGO GdOjf, CMeO Hf Rjf GdOjf Hf EHQGgje Hf UbQ, J (B1241(3g`s ((3eMeO bdj Hf ejQRG GdNhFjfjs)
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf(B... (3CeG HYO ajbhd GdYHO GdeScjf CMeO Hf Rjf GdOjf GdCMSGFj Efg YQV Ydj LfGH GdaGVd (B...s
(3BNQgG (B:s
(3hEf cfJ CYJbO aSGOg Ch CHjfg HeG CYJbO aEf bdJ Hd HeG JYJbO agcPG hGddg aYdJ(B. (3heG Jhajbj EdG HGddg GdYXje(B...s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: (3L(B1(3, U(B129s
(3gOjI GdYGQajf(B: (3L(B1(3, U(B185s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds